The effect of immediate and delayed post-space preparation using extended working time root canal sealers on apical leakage - G. Chen; Y.C. Chang (Elsevier, 2013)
Background/purpose: The purpose of this study was to compare the effect of different post-space preparation time intervals on the apical sealing ability of filling material using two different extended setting time root canal sealers. Materials and methods: A total of 100 single-canal teeth were incrementally cleaned with crown-down instrumentation using K3 rotary nickel-titanium instruments and randomly divided into four groups. There were 30 teeth in the experimental groups (Groups 1-3) and 10 teeth in the control group (Group 4). We obturated the teeth using a warm gutta-percha vertical compaction technique with pulp canal sealer (Group 1), Tubli-Seal EWT (Group 2), and pulp canal sealer EWT (Group 3). We then stored all the specimens in 100% humidity at 37°C for 1 week. We used heated pluggers to create post space at three different intervals postobturation (i.e., immediately after obturation, on Day 3, and on Day 7), leaving 5-mm gutta-percha filling at the apices. We then immersed the teeth in 2% methylene blue solution for 72 hours, and finally sectioned them longitudinally into two halves. The amount of apical dye leakage was measured under a stereomicroscope. Results: The results showed no significant difference (P > 0.05) in dye leakage between the standard and extended working time root canal sealers. Apical leakage tended to increase more severely in Group 1 at the three different intervals was considered. Conclusion: Extended working time root canal sealers do not affect microleakage results using a warm gutta-percha vertical compaction technique. The sealing ability of extended working time root canal sealers on high heat conditions is as good as the standard working time root canal sealer during post-space preparation of different intervals.